PRE-DESIGN OF BIODEGRADABLE FOAM INDUSTRY AS PACKAGING FOR GRAPES (VITIS VINIFERA L.) ON A RETAIL SCALE: CHARACTERISTICS OF BIODEGRADABLE FOAM PACKAGING BASED ON CORN STARCH (MAIZE) AND CORN HUSK WITH THE ADDITION OF CHITOSAN USING THE THERMOPRESSING METHOD - Naufal Haitami, Muhammad
Biodegradable foam is an environmentally friendly packaging as an alternative to Styrofoam. Cornstarch-based biodegradable foam has good expandability. The addition of corn husk powder, polyvinyl alcohol (PVA), and magnesium stearate can increase mechanical strength and reduce water absorption. However, biodegradable foam has not been able to replace Styrofoam in terms of mechanical strength and water absorption. The addition of chitosan is expected to increase mechanical strength and reduce water absorption. This study aims to determine the best chitosan concentration as a substance that can increase mechanical strength and reduce water absorption of biodegradable foam. This study used a completely randomized design (CRD) with five treatments and four replicates. The chitosan concentrations used in this study include 0%, 7%, 8%, 9%, and 10%. The data obtained were analyzed using ANOVA test with 5% significance level and Tukey's further test. The research began with making corn husk powder and continued with molding. After the packaging was successfully printed, several tests were carried out, including density, water absorption, water content, tensile strength, and degradability. After testing, the results showed that biodegradable foam with a chitosan concentration of 10% was the biodegradable foam with the best characteristics because it had a tensile strength of 1.37 MPa, density of 0.274 g/cm3, air content of 0.27%, air absorption capacity of 75.97 %, and the degradability level is 48.95%. K